Sediment-Derived Dissolved Organic Matter Stimulates Heterotrophic Prokaryotes Metabolic Activity in Overlying Deep Sea in the Ulleung Basin, East Sea - Hyun, Jung-Ho; Kim, Bomina; Han, Heejun; Baek, Yong-Jae; Lee, Hyeonji; Cho, Hyeyoun; Yoon, Seok-Hyun; Kim, Guebuem (Frontiers in Marine Science, 2022)
The effects of benthic dissolved organic carbon (DOC) flux on the dynamics of DOC in the deep continental margins (200 – 2000 m depth) is poorly understood. We investigated heterotrophic prokaryotes (hereafter bacteria) production (BP) and the bio-reactive properties of sediment-derived dissolved organic matter (SDOM) to elucidate microbially mediated cause-effect relationships regarding the rapid consumption of dissolved oxygen (DO) and accumulation of humic-like fluorescent DOM (FDOMH) in the deep-water column (750 – 2000 m depth range) of the Ulleung Basin (UB) in the East Sea. BP in the deep water (2.2 μmol C m-3 d-1) of the UB was among the highest reported for various deep-sea sites. The high DOC concentration (55 μM) likely supported the high BP seen in the deep-water column of the UB. Concentrations of DOC and C1 component of the FDOMH, which is indicative of microbial metabolic by-products, were 13-fold and 20-fold greater, respectively, in pore water than in the overlying bottom water, indicating that the sediment in the continental margins is a significant source of DOM in the overlying water column. Fine-scale water sampling revealed that BP near the sediment (0 – 30 m above the seafloor; 2.78 μmol C m-3 d-1) was 1.67 times higher than that measured in the water column above (30 – 100 m above the seafloor; 1.67 μmol C m-3 d-1). In addition, BP increased in the bottom water incubation amended with SDOM-containing pore water (PW). The results demonstrated that SDOM contains bio-reactive forms of DOM that stimulate heterotrophic microbial metabolism at the expense of oxygen in the bottom water layer. The accumulation of C1 component in both PW-amended and unamended bottom water incubation (i.e., without an extra DOM supply from sediment) further indicated that refractory DOM is produced autochthonously in the water column via heterotrophic metabolic activity. This explains in part the microbially mediated accumulation of excess FDOMH in the deep-water column of the UB. Overall results suggest that the benthic release of bio-reactive DOM may be of widespread significance in controlling microbial processes in the deep-water layer of marginal seas.